Are all the 18 DSM-IV and DSM-5 criteria equally useful for diagnosing ADHD and predicting comorbid conduct problems? - Rosales, Alexandra Garcia; Banaschewski, Tobias (European child & adolescent psychiatry, 2015)
In view of ICD-11 revision, we evaluate whether the 18 DSM-IV diagnostic items retained by DSM-5 could be further improved (i) in predicting ADHD ‘caseness’ and ‘impairment’ and (ii) discriminating ADHD without CD (ADHD − CD) cases from ADHD with CD (ADHD + CD) cases. In a multi-centre study sample consisting of 1497 ADHD probands and 291 unaffected subjects, 18 diagnostic items were examined for redundancy; then each item was evaluated for association with caseness, impairment and CD status using Classical Test Theory, Item-Response Theory and logistic regression methods. First, all 18 DSM-IV items contributed significantly and independently to the clinical diagnosis of ADHD. Second, not all the DSM-IV items carried equal weighting. “Often loses things”, “forgetfulness” and “difficulty sustaining attention” mark severity for Inattentiveness (IA) items and “often unduly noisy”, “exhibits a persistent pattern of restlessness”, “leaves seat in class” and “often blurts out answers” for Hyperactivity/Impulsivity (HI) items. “Easily distracted”, “inattentive to careless mistakes”, “often interrupts” and “often fidgets” are associated with milder presentations. In the IA domain, “distracted” yields most information in the low-severity range of the latent trait, “careless” in the mid-severity range and “loses” in the high-severity range. In the HI domains, “interrupts” yields most information in the low-severity range and “motor” in the high-severity range. Third, all 18 items predicted impairment. Fourth, specific ADHD items are associated with ADHD + CD status. The DSM-IV diagnostic items were valid and not redundant; however, some carried more weight than others. All items were associated with impairment.